A fresh look at the structural, ferroelectric and photoluminescent properties in perovskites - Andrés, Juan; Longo, V. [UNESP]; Cavalcante, L. [UNESP]; Moreira, M. L. [UNESP]; Varela, J. [UNESP]; Longo, E. [UNESP] (My University, 2012)
The perovskite based materials ABO3 are in huge expansion worldwide. Fundamental scientific studies on perovkite materials have been carried out intensively due to their unique dielectric, piezoelectric, and ferroelectric properties, which are of great interest in the technological applications such as capacitors, transducers, sensors, actuators, and nonvolatile random-access memory devices. The synthesis, characterization and study of ferroelectric and photoluminescence properties of perovskite metal oxides have been the subject of a number of recent researches and the corresponding electronic structures have been studied quite extensively by experimental or/and theoretical works. The history of structural analysis of perovskites material gives the basis for a deeper understanding of its properties and the same flexibility that make possible the fascinating ferroelectric properties make the photoluminescence to arrive. The modulated ferroelectric and luminescence properties of these perovskite-based materials provide for a fundamental understanding of the intrinsic optical and optoelectronic properties of these systems, suggesting, therefore, the possibility of their rational incorporation into functional nanoscale devices. To this end, in this work is presented an understanding on the structural, ferroelectric and photolumiscence properties in perovskite-based materials. © 2012 Nova Science Publishers, Inc.
Keywords: Ferroelectric; Perovskite-based materials; Photoluminescence; Theoretical calculations